A Comparison of Free and Mapped Meshes for Static Structural Analysis - Haider Aun (Fatigue of Aircraft Structures)
This study addresses the challenge faced by Finite Element Analysts when choosing between free and mapped meshes, especially in terms of convergence stability and solution accuracy. The investigation focuses on 3D solid models under static structural loading, analyzed using Ansys® and MSC Patran®. Both free and mapped mesh types, employing equivalent 3D solid elements, are used to assess an aircraft structural component under design load conditions, with fixed boundaries. For free meshes, Tet10 elements in Patran (equivalent to Solid 72 in Ansys) are used, whereas for mapped meshes, CPENTA / CHEXA elements in Patran (equivalent to Wed6 / Hex8 in Ansys) are employed. Mesh convergence studies ensure that discretization does not affect the numerical solution. Notably, a significant stress increase is observed with successive refinement of free meshes, while mapped meshes achieve mesh independence at coarser refinement levels. Comparison of fringe plots indicates the same location for maximum deformation and equivalent stress in both free and mapped mesh models. The findings demonstrate that free meshes tend to underpredict maximum deformation and equivalent stress compared to mapped meshes, with both meshes showing deformation and stress at consistent locations. The findings underscore the importance of carefully choosing the appropriate mesh type, particularly when analyzing critical structural components, to ensure reliability and accuracy in FEA simulations.